'The Empire Strikes Back' ?: HGIS de las Indias and the Postcolonial Death Star*. Issue 2 (October 2018) - Stangl, Werner
Abstract : This article serves a two-fold purpose: first, to give an overview of the project HGIS de las Indias, and second to ask for its relation with the epistemological currents in spatial humanities, thereby raising some fundamental thoughts and inquietudes about the relationship between projects designed for accommodating particular practical needs and overarching theory. In the first part, thus, we will sketch the initial impulse that made the project come to life; then, we will outline the basic structure, features, and general characteristics of the database and its web application, briefly commenting on how that database design correlates and conflicts with the ontologies of historical sources underlying the reconstruction process. In the second part, we will try to tackle the question of whether projects of such tailoring should have a place within the spatial humanities, which seem to have shifted or solidified their epistemological center in poststructuralist, postmodern, postcolonial, and neo-geographic discourses, advocating for a reflected employment of digital spatial tools focussing on their different roles within the humanities instead of enforcing a growing divide between a theoretical navel-gazing and an atheoretical practice.